Analisis Efektivitas, Efisiensi, Dan Kontribusi Penerimaan Pajak Daerah Dan Retribusi Daerah Terhadap Pendapatan Asli Daerah Kota Makassar - Fitri , Asriyanti Nur; Afifah , Nurul; Ka, Veronika Sari Den (PT Bone Jaya Kreatif, 2023)
This study aims to determine the effectiveness of Makassar City local tax receipts, the effectiveness of Makassar City's regional retribution receipts,the contribution of local taxes to Makassar City's local revenue, the contribution of regional levies to Makassar City’s regional original revenues, and the efficiency of local tax and regional retribution revenue in Makassar. This research is a type of quantitative research with a descriptive analysis approach. This research uses primary data and secondary data. The results of the study showed that the effectiveness of regional tax revenues in 2017-2019 is quite effective, in 2019 and 2021 it is the most effective. The effectiveness of regional retribution revenue in 2017-2019 is not effective, in 2020 and 2021 it is the most effective. The contribution of local taxes to Makassar City's local revenue from 2017-2021 is the most contributed category. The contribution of regional retribution to Makassar City's original revenue from 2017-2021 is very less. And the efficiency of regional tax revenue and regional levies in 2017-2021 is rarely efficient. Effectiviness, efficiency, and the contribution of regional taxes and regional retributions can increase regional original income by making various efforts, and managing costs to be incurred so that they are less than revenues.